1971
DOI: 10.1073/pnas.68.8.1848
|View full text |Cite
|
Sign up to set email alerts
|

DNA Uptake during Genetic Transformation and the Growing Zone of the Cell Envelope

Abstract: Continuous cellular incorporation of choline molecules is essential for DNA binding to competent pneumococci. The choline molecules are incorporated into the cell surface at the equatorial region of the cocci. As a working hypothesis, it is proposed that DNA molecules enter these bacteria at the growing zone(s) of the cell envelope.The presence of choline residues in the teichoic acid portion of the pneumococcal cell envelope (1) is essential for several physiological functions of this bacterium. Not only is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

1974
1974
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 14 publications
3
25
1
Order By: Relevance
“…In a different study, Tomasz and colleagues took advantage of the fact that choline-containing cell wall is sensitive to autolysin whereas ethanolamine-containing cell wall is not. Autolysin treatment of choline-pulsed ethanolamine-grown cells confirmed that new cell wall is inserted in the central portion of dividing cells (187,188). These results were recently supported by Van-FL staining of S. pneumoniae, which clearly indicated PG synthesis activity at the septal and (stained less brightly) the equatorial rings (31).…”
Section: Pbp2xsupporting
confidence: 61%
“…In a different study, Tomasz and colleagues took advantage of the fact that choline-containing cell wall is sensitive to autolysin whereas ethanolamine-containing cell wall is not. Autolysin treatment of choline-pulsed ethanolamine-grown cells confirmed that new cell wall is inserted in the central portion of dividing cells (187,188). These results were recently supported by Van-FL staining of S. pneumoniae, which clearly indicated PG synthesis activity at the septal and (stained less brightly) the equatorial rings (31).…”
Section: Pbp2xsupporting
confidence: 61%
“…It is possible that the CiaRH system is also involved in licD2 expression under choline starvation, but further experiments are required to reveal the relation between CiaRH, the licD2 product, and cellular lysis. Interestingly, cells also respond to choline deprivation with a rapid decline of cellular competence (52), another indication that the cia system might be activated and indeed required under these conditions.…”
Section: Vol 188 2006mentioning
confidence: 99%
“…The other domain, located at the N terminus, is probably directly responsible for the lytic activity against pneumococcal peptidoglycan structures. Attachment of the enzyme to the choline of the S. pneumoniae cell wall teichoic acid is essential for the lytic activity of the enzyme (155). The carboxy-terminal attachment module probably influences the activity of the enzyme by stabilizing or inducing its active conformation (17).…”
Section: Autolysinmentioning
confidence: 99%
“…Examples of other pneumococcal CBPs are the major cell wall hydrolase LytA (54) and an adhesin choline binding protein A (CbpA) (129). LytA is an amidase functioning in the separation of daughter cells during cell division (127) and is required for cell lysis (155), whereas CbpA appears to be the first known protein adhesin on the pneumococcal surface (129). The CBR motif has also been found among the surface proteins of other bacteria (164) like Clostridium acetobutylicum, Clostridium difficile, Streptococcus mutans, and Streptococcus downei.…”
Section: Attachment To the Surface Of S Pneumoniaementioning
confidence: 99%